Analisis Penguraian Masalah pada Program Zakat Produktif - Widya Francisca Fitriani; Anita Priantina (Department of Islamic Economics, IPB University, 2016)
. Productive zakah program that run by BAZNAS and LAZ was a real contribution to reduced poverty. Productive zakat aimed to made mustahiq became more productive. However, these goals had not been achieved maximum. There were two main problems in running productive zakah program. They were problem from internal party of BAZNAS/LAZ and problem from external party of BAZNAS/LAZ. Among the internal problems were: 1) Immaturity of program planning, 2) Less of capable human resources, 3) No fixed success indicators. The external problems were: 1) Lack of zakat institution management, 2) Lack of entrepreneurial spirit among mustahiq, 3) Mustahiq was not understand about the rule of productive zakah program. This study concluded that the dominant problem was an internal problem of the BAZNAS / LAZ –with priority problem lied in 'immaturity of program planning'